THE RELATIONSHIP OF BIOCHEMICAL MARKERS AND COAGULATION PROFILES WITH THE SURVIVAL STATUS AMONG COVID-19 PATIENTS - Mohamad Samuri , Nurul Farah Syahidah; Mohd Kasim, Noor Alicezah; Isa, Mohamad Rodi; Abdul Monir, Madyhah; Mohd Rosli , Marshima; Yusoff, Nur Amalina; Khairul Atikah, Sharifah (Malaysian Journal of Public Health Medicine, 2024)
The Coronavirus Disease of 2019 (COVID-19) is an imminent threat to world health, and effective management of COVID-19 patients is needed. Biochemical markers and coagulation profiles are required for medical intervention and prediction of morbidity and mortality. This study aims to determine the relationship between biochemical markers and coagulation profiles with the survival status among COVID-19 patients. A cross-sectional study using secondary data was conducted among 470 COVID-19 patients admitted to Hospital Sungai Buloh from April 2021 to July 2021. The biomarkers include C-reactive protein (CRP), ferritin, procalcitonin (PCT), lactate dehydrogenase (LDH), D-dimer, high-sensitivity troponin I (hs-Trop I), creatine kinase (CK), sodium, potassium, urea, creatinine, alanine transaminase (ALT), aspartate aminotransferase (AST), albumin, total bilirubin, activated partial thromboplastin time (APTT) and prothrombin time (PT) along with survival status were extracted from the hospital electronic medical records. The relationship between biomarkers with the survival status among COVID-19 patients was analysed using simple and multiple logistic regression. The results showed an increased odd of mortality in deceased patients, particularly in PCT with an odds ratio (OR) of 1.028 (95%CI: 1.001, 1.055), LDH with an OR of 1.002 (95%CI: 1.001,1.003), and urea with an OR of 1.070 (95%CI: 1.034,1.107) compared to survivors. All three biomarkers give 98.7% sensitivity and 13.0% specificity with the area under the curve (AUC) of 0.762 (95%CI: 0.705, 0.820). In summary, our research underscores a significant correlation between the mortality risk of COVID-19 patients and increased PCT, LDH, and urea.